ANALISIS KEBUTUHAN BUKU AJAR PERCAKAPAN BAHASA JEPANG YANG BERORIENTASI HOSPITALITY BAGI MAHASISWA PROGRAM INTERNSHIP D3 BAHASA JEPANG UTY - Kastuti, Teti Indriati (Journal of Japanese Language Education and Linguistics, 2018)
Hospitality is one of materials in gaido course. The research objective is to analyse the need of developing gaido instructional material which oriented to hospitality for students of  D3 Japanese at Univeristy of Technology Yogyakarta especially students who will take internship program as the basis of instructional material development in the future. This research belongs to descriptive qualitative research. Analysis stage refers  to analyze step in ADDIE development model. Data collecting technnique is conducted through questionnaire distribution, observation, and interview. From the interview with students who are taking intership program, it finds that: (1) speaking skill of students who taking internship program is till low since the course material has not facilitate the need of of those students (2) one of the efforts to improve speaking skill of students who taking internship program is by providing conversation instructional material which oriented to hospitality (3)to develop conversation instructional materialwhich is oriented to hospitality needs the latest literature source so students are able to implement in real situation setting directly.Keyword:hospitality, instructional material, ADDIE